Quirópteros da Estação Ecológica de Santa Bárbara no Cerrado paulista: inventário e pesquisa da circulação do vírus da raiva - Rodrigues, Ana Claudia (Universidade Federal de São Carlos, 2023)
The Cerrado is one of the largest and richest Brazilian domains and has been suffering intense degradation, pointing to the urgency in the preservation and restoration of its areas. The EESB (Estação Ecológica de Santa Bárbara) is a conservation unit located in Águas de Santa Bárbara, São Paulo State, which covers an area of 2,712 ha and preserves different typical Cerrado physiognomies. Knowing the high diversity of bats that occurs in the Cerrado, and recognizing their important ecological roles and the influence of these species on public health, we aimed to inventory the bats in the EESB to obtain data on the composition and richness of species in this UC, as well as to investigate the prevalence of rabies in the specimens collected, contributing to the epidemiological monitoring of the region. Sampling was conducted during the rainy season, from October to December 2021, and from February to March 2022. The Chiroptera were sampled at 30 distinct points during 30 nights, totaling an effort of 54,000 meters2.net.hour. Individuals were identified as to species, sex, and reproductive status from examination of qualitative and quantitative characteristics of external morphology, skull-dental, and internal anatomy. We sampled 223 individuals representing 20 species and 14 genera of the families Phyllostomidae (129 specimens, 10 species), Vespertilionidae (84, 8), and Molossidae (10, 2), obtaining two new records for the species Myotis lavali and Myotis izecksohni for the state, as well as morphological data and data concerning the reproductive season and offspring size for several species. These data contribute to future taxonomic and systematic studies, increasing the representativeness of samples from São Paulo, as well as with valuable ecological data, helping to evaluate the conservation status of these species in São Paulo, supporting the relevance of the EESB in preserving the Cerrado and its fauna. Blood samples were collected via cardiac puncture for rabies seroprevalence analysis (60 specimens, 15 species), and brain samples were collected via foramen magnum puncture (114, 16) from euthanized specimens (116 - 52% of total captures). Gut samples for coronavirus testing, liver samples for DNA extraction, and blood samples for leishmaniasis culture were also collected for most of the euthanized specimens for future studies. These specimens were wet-preserved, with skulls extracted from 116 specimens, which will be deposited in the Mammal Collection of the Museum of Zoology of the University of São Paulo. The released individuals were marked by cutting the interfemoral membrane, and these samples, as well as the liver samples, were kept at the Laboratory of Mammal Systematics (LASISMA), UFSCar for future molecular analysis. The Laboratory of Zoonoses and Vector-borne Diseases (LABZOO) in São Paulo performed the rabies laboratory tests. For quantification of antibodies in blood samples, the serum neutralization method (SNSF) was applied, and for virus detection in brain samples, direct immunofluorescence (DFI) and isolation by cell culture were performed, with negative results for both seroprevalence and rabies virus diagnosis. These results raise interesting discussions about how these pathogens relate to populations in native vegetation and protected areas, highlighting the importance of UCs in the control and dissemination of zoonoses.
Chiroptera from the Santa Bárbara Ecological Station in the Cerrado of São Paulo: inventory and research on rabies virus circulation
Keywords: Biodiversidade; Cerrado; Conservação; Morcegos; Zoonose; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONSERVACAO DAS ESPECIES ANIMAIS